Cervical cancer: knowledge, attitude and practice on the prevention examination - Ester Marcele Ferreira de Melo; Francisca Márcia Pereira Linhares; Telma Marques da Silva; Cleide Maria Pontes; Alessandro Henrique da Silva Santos; Sheyla Costa de Oliveira
ABSTRACT Objective: to evaluate the knowledge, attitude and practice of women on the cervical-uterine cancer screening and to investigate their association with sociodemographic variables. Method: a cross-sectional study, carried out from July to September 2015, with 500 women enrolled in the Basic Health Units of the Health District V, of the city of Recife-PE. For data collection, a semi-structured form was used. In statistical analysis, the Chi-square test and Fisher's Exact Test were applied and, in the multivariate analysis, the Poisson model and Wald statistic. Results: the prevalence of adequate knowledge, attitude and practice was 35.2%, 98% and 70.6%, respectively. Adequate knowledge was associated with having no children, having a family income of two minimum wages and Spiritist/Afro-Brazilian religion. Conclusion: women carry out the examination, deem it necessary, but do not have adequate knowledge, which demonstrates the need for educational actions by nurses and other health professionals.